Enhancing Tofu Product Development: Integrating KANO and QFD Models for Consumer-Driven Satisfaction: Meningkatkan Pengembangan Produk Tahu: Mengintegrasikan Model KANO dan QFD untuk Kepuasan yang Dikendalikan oleh Konsumen - Hidayat, Anastasya Putri; Sukmono, Rita Ambarwati (Universitas Muhammadiyah Sidoarjo, 2023)
This study seeks to optimize product development within the tofu industry by synthesizing the KANO and Quality Function Deployment (QFD) models, leveraging consumer preferences as the cornerstone for classification and gauging their profound influence on overall customer satisfaction. Employing a quantitative approach with a descriptive framework, this research employs the KANO model and Quality Function Deployment (QFD) as analytical methodologies. The outcomes unveil a structured approach that effectively aligns product attributes with consumer expectations, thereby enhancing customer satisfaction in the tofu market. This study's implications underscore its potential to revolutionize the tofu industry's product development strategies, emphasizing a consumer-centric approach for global applicability. Highlights: Integration of KANO and QFD: Efficient fusion of KANO and QFD models for enhanced product development. Consumer-Centric Approach: Prioritizing consumer preferences to boost customer satisfaction. Industry Transformation: Potential to revolutionize tofu product development strategies globally. Keywords: Tofu, Product Development, KANO Model, QFD, Consumer Preferences